2017
DOI: 10.5114/aoms.2016.62869
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal cognitive changes and androgen levels in the context of apolipoprotein E polymorphism

Abstract: IntroductionThe focus of this study was to assess cognitive functions in relation to androgens and specifically testosterone and dehydroepiandrosterone in postmenopausal women as well as the correlation between cognitive functions and these two androgens according to polymorphism of the apolipoprotein E gene (APOE).Material and methodsA group of 402 women was recruited to the study (minimum 2 years after the last menstruation, follicle-stimulating hormone (FSH) more than 30 U/ml and no dementia signs on Montre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…In addition, an enhanced negative effect of testosterone on cognition was found in postmenopausal women with at least one APOE ε4 allele [31].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, an enhanced negative effect of testosterone on cognition was found in postmenopausal women with at least one APOE ε4 allele [31].…”
Section: Discussionmentioning
confidence: 96%
“…It was also demonstrated that in post-menopausal women the correlation between CRP level and cognitive functions may be modified by apolipoprotein E genotypes [ 30 ]. In addition, an enhanced negative effect of testosterone on cognition was found in postmenopausal women with at least one APOE ε4 allele [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, testosterone therapy improved the physical and emotional well-being as well as sexual function of postmenopausal women [6668]. Conversely, in the group of postmenopausal women, higher testosterone concentration was associated with lower scores for verbal and visual memory, processing and psychomotor speed, executive functions, complex attention and cognitive flexibility [69].…”
Section: Discussionmentioning
confidence: 99%
“…Problems related with cognitive functions, increasing with age, are presented in many studies. Going through the menopause in women is also 2 Arch Med Sci associated with a clear decline in cognitive functioning [1,2]. It is still difficult to state the causes for the deterioration of cognitive functioning in women during this period of life.…”
Section: Introductionmentioning
confidence: 99%